The complete chloroplast genome of Dictamnus dasycarpus Turcz. (Rutaceae) - Yan-ping Xing; Yue-yue Song; Yan-yun Yang; Che Bian; Wen-xiao Men; He-fei Xue; Liang Xu; Ting-guo Kang (Mitochondrial DNA. Part B. Resources, 2022)
Dictamnus dasycarpus Turcz. 1842 is a medicinal plant of China. Its dry root bark is called BAIXIANPI, which is a common traditional Chinese medicine. Here, we report the complete chloroplast genome of D. dasycarpus. The length of the genome, large single-copy (LSC), small single-copy (SSC), inverted repeat (IR), and GC content was 157,056 bp, 84,497 bp, 18,487 bp, 27,036 bp, and 38.5%, respectively. A total of 132 genes were annotated, including 87 protein coding, eight rRNA, and 37 tRNA genes. Interestingly, 15 genes contained single intron while two others contained two introns. The phylogenetic tree showed the two D. dasycarpus (D. albus) clustered in a clade, which was sister to clade formed by the species of Melicope, Tetradium, Phellodendron, and Zanthoxylum.